Analisis Raskin dan Ketahanan Pangan Rumah Tangga di Indonesia (Analisis Data Susenas 2011) - Sundari, Irma; Nachrowi, Nachrowi Djalal (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
This study aims to analyze the food security determinant of households by household characteristics in Indonesia using descriptive and multinomial logit analyses, and determine the characteristics of households that need intervention of Raskin in Indonesia. Descriptive and multinomial logit analyses found that households more food secure if the education of household head is higher, number of household members is smaller, the household head work in non-agriculture, income per capita is larger, and the area where household live in urban areas. Generally, Raskin relatively on target. Raskin should be prioritized on women-headed households with low education, and work in agriculture/non-agriculture.